Sur la première carte des flux réalisée avec des flèches (Ravenstein, 1885) - Françoise Bahoken (Confins)
The map entitled « Currents of Migration » performed by Ravenstein when he published his Laws of Migration for the first time in 1885, seems to be the first flow map with arrows. This 5th Ravenstein’s map is very particular because it is not called in the text and it has no elements that allow us to understand exactly what movement is depicted and how it is represented. We just know that it illustrates internal migrations laws that are so complex to formulate and to depict. In order to enlighten this first flow map with arrows, we present here an analysis focused on both historical and methodological practices of aggregated flow mapping. In fact, probably made from Origin-Destination census data on United Kingdom mobility (1871-1881), Map no.5 of Ravenstein (1885) breaks new ground in both the graphic process used in the mapping approach and the conceptual implementation we offer. If the historical context of the realization of this map is on discrete statistical mapping, Ravenstein offers a figure which seems based on physical principles. Here, the author is like to have applied a continuous flow mapping process within a spatial approach of statistical cartography. Firstly, the innovation is then to have introduced the idea on an apparently continuous movement mapping approach. Secondly, it is to have implemented in a map the principles of spatial interaction patterns before they were conceptually formulated. Thirdly, Ravenstein apparently uses the arrow process in new ways and even in unusual form for us since it does not seem to connect the centers of both origins and destinations places (with the process of flows that converge to a place): it seems to mark only the administrative transboundary movement between neighboring areas. That is why we can consider this map as likely to renew the current practice of flow mapping.